biology Effect of Adding Microorganisms on the Degradation of Phenolic Compounds in Olive Mill Wastewater - Al-Sayed, Daowd; Kridi, Nabila; Al-Shater, Mohammed Saeed (Iraqi Journal of Science, 2022)
Bio-treatment is considered as one of ecologically most efficient methods of wastewater treatment. This study was done in order to reduce the negative effects phenolic compounds included in the olive mill wastewater added to the cultivated soil and to study the individual and collective ability of fungal and bacterial isolates to dismantle them. The experiment, conducted in 2020 with randomization in experimental design, consisted of six treatments and three replications. First four treatments had olive mill wastewater treated with fungal isolates Penicillium sp, Aspergillus flavos and bacterial isolates Pseudomonas sp,Bacillus sp individually. The fifth treatment included collective use of both isolates, in addition to the control which was without any treatment. The results of the statistical analysis showed that the phenolic compounds amount remained in the treated water which indicated the superiority of Penicillium sp over all treatments, where the apparent superiority of phenolic compounds dismantling was over bacterial isolates. However it was significantly over the collective effects of fungal and bacterial isolates, Aspergillus flavos and the control.